(untitled) - Frowen, Stephen F. (New York, 2004)
This volume contains the correspondence between G.L.S. Shackle and S.F. Frowen from the time Shackle took up his first post-war academic appointment until his death in 1992. The correspondence, partly personal and partly professional, reveals a vital insight into Shackle both as a man and as an outstanding economist.
Keywords: Shackle, G. L. S. (George Lennox Sharman), 1903 -,Frowen, Stephen F.,Economists,Economics,Decision making,Economists; Correspondence,Correspondence,Correspondence,Philosophy,Biography; Great Britain,Great Britain